Insights from native mass spectrometry approaches for top- and middle- level characterization of site-specific antibody-drug conjugates. Issue 5 (4th July 2017) - Botzanowski, Thomas; Erb, Stéphane; Hernandez-Alba, Oscar; Ehkirch, Anthony; Colas, Olivier; Wagner-Rousset, Elsa; Rabuka, David; Beck, Alain; Drake, Penelope M.; Cianférani, Sarah
ABSTRACT: Antibody-drug conjugates (ADCs) have emerged as a family of compounds with promise as efficient immunotherapies. First-generation ADCs were generated mostly via reactions on either lysine side-chain amines or cysteine thiol groups after reduction of the interchain disulfide bonds, resulting in heterogeneous populations with a variable number of drug loads per antibody. To control the position and the number of drug loads, new conjugation strategies aiming at the generation of more homogeneous site-specific conjugates have been developed. We report here the first multi-level characterization of a site-specific ADC by state-of-the-art mass spectrometry (MS) methods, including native MS and its hyphenation to ion mobility (IM-MS). We demonstrate the versatility of native MS methodologies for site-specific ADC analysis, with the unique ability to provide several critical quality attributes within one single run, along with a direct snapshot of ADC homogeneity/heterogeneity without extensive data interpretation. The capabilities of native IM-MS to directly access site-specific ADC conformational information are also highlighted. Finally, the potential of these techniques for assessing an ADC's heterogeneity/homogeneity is illustrated by comparing the analytical characterization of a site-specific DAR4 ADC to that of first-generation ADCs. Altogether, our results highlight the compatibility, versatility, and benefits of native MS approaches for the analytical characterization of all types of ADCs, including site-specific conjugates. Thus, we envision integrating native MS and IM-MS approaches, even in their latest state-of-the-art forms, into workflows that benchmark bioconjugation strategies.